KADAR TRIGLISERIDA DAN STATUS GIZI PADA KLIEN TUBERKULOSIS - Diani, Noor; Rahmayanti, Devi (School of Nursing, Faculty of Medicine and Health Science, Universitas Lambung Mangkurat, 2017)
Tuberculosis(TB) resulting the decreasing of nutrient intake and malabsorbsi as well aschanging the metabolism of the body. The wasthing are decreased protein energy. Malnutritionon TB affects the prognosis of the treatment and death rates. The increase TNF α will inhibit theenzyme activity of Lipoprotein Lipase (LPL) in the fat tissue. LPL enzyme plays a role in cleavageprocess of triglycerides. This research was to analyze the relationship of triglycerides andnutrition status on the client with tuberculosis. The design was cross-sectional approach. Therespondents were gathered from 25 newly TB patients. The analyzed using Pearson ProductMoment correlation. The results showed 56% respondents undernutrition, and normal 40% andover nutrition 4%. Most triglyceride level of the respondent were normal (84). The concludedwas a relationship between triglycerides and the nutritional status with a positive correlation ( Pvalue 0,396).